Use of the modified meek technique for the coverage of extensive burn wounds - Tapking, Christian; Panayi, A.; Haug, V.; Palackic, A.; Houschyar, K. S.; Claes, K. E. Y.; Kuepper, S.; Vollbach, F.; Kneser, Ulrich; Hundeshagen, Gabriel (Burns, 2024)
Introduction - Autologous split thickness skin grafting using meshing technique remains the preferred option for the management of deep dermal and full thickness burns. The limited donor site availability seen in patients with extensive burns, however, restricts use of the mesh grafting technique for skin expansion. Meek micrografting was developed to allow for greater expansion, and, therefore, more reliable treatment of extensive burns. This study aimed to present our outcomes using the Meek micrografting technique and identify risk factors for graft failure. - Methods - A retrospective review of patients admitted to our large academic hospital who were treated with the Meek micrografting technique from 2013 to 2022 was conducted. Patient demographics, surgical characteristics and outcomes were reported. Regression analyses were performed to identify factors that influence graft take and reoperation rate. - Results - A total of 73 patients with a mean age of 45.7 ± 19.9 years and mean burn size of 60.0 ± 17.8%TBSA, with 45.3 ± 14.9% TBSA being third degree burns, received Meek transplantation. The mean graft take after removal of the pre-folded polyamide gauze at the tenth post-operative day was 75.8 ± 14.7%. Pre-treatment with use of an allograft, longer waiting time between admission and Meek grafting and transplantation over a dermal matrix were identified as positive predictors for graft take, while age was established as a negative predictor. - Conclusion - By examining the outcomes of the Meek micrografting technique in extensive burn wounds we identified that preconditioning of the wound bed, through allograft or negative pressure wound therapy application, positively correlates with improved outcomes, including higher graft take. At the same time, older age was seen to negatively correlate with graft take. Overall, Meek transplantation displays a favorable safety profile with promising outcomes. Future prospective studies and clinical trials can optimize the procedure and help establish it as the golden standard for extensive and complex burns.
Online verfügbar: 15. Januar 2024, Version des Artikels: 24. April 2024
Gesehen am 13.11.2024